Early Dynamics and Depth of Response in Multiple Myeloma Patients Treated With BCMA CAR-T Cells - Wong, Sandy W.; Shah, Nina; Ledergor, Guy; Martin, Thomas; Wolf, Jeffrey; Shui, Amy M.; Huang, Chiung-Yu; Martinez-Lopez, Joaquin (Frontiers in Oncology, 2021)
Chimeric antigen receptor T-cell (CAR-T) therapy targeted against B-cell maturation antigen (BCMA) in multiple myeloma (MM) has produced rapid responses but many eventually relapse. In light of this new treatment, novel predictors of progression-free survival (PFS) are needed. We performed a single institution analysis of 54 BCMA-CAR-T patients. We analyzed patient’s overall response rate (ORR) by the IMWG criteria, involved serum-free light chains (iFLC), and minimal residual disease testing by next-generation sequencing (MRD-NGS). Between patients who achieved a ≤SD and those who achieved a ≥PR, PFS differed significantly (p < 0.0001); though there was no difference between patients who achieved a ≥CR vs. VGPR/PR (p = 0.2). In contrast, patients who achieved a nonelevated iFLC at 15 days (p < 0.0001, HR = 6.8; 95% CI, 2.7–17.3) or 30 days (p < 0.001, HR = 16.7; 95% CI, 3.9–71.7) had a prolonged PFS compared with those with an elevated iFLC. Patients achieving MRD-NGS less than the detectable limit at a sensitivity of 10−6 had a better PFS than those with detectable disease at 1 month (p = 0.02) and 3 months (p = 0.02). In conclusion, achieving a nonelevated iFLC and an undetectable MRD-NGS quickly were factors that were strongly associated with improved PFS. Further studies are needed to confirm the role of these markers in MM patients receiving CAR-T therapies.